Access to divalent lanthanide NHC complexes by redox-transmetallation from silver and CO2 insertion reactions. Issue 2 (7th December 2018) - Simler, Thomas; Feuerstein, Thomas J.; Yadav, Ravi; Gamer, Michael T.; Roesky, Peter W.
Abstract : Divalent NHC–lanthanide complexes were obtained by redox-transmetallation. Treatment with CO2 led to insertion reactions without oxidation of the metal centre. Abstract : Through a redox-transmetallation procedure, divalent NHC–Ln II (NHC = N-heterocyclic carbene; Ln = Eu, Yb) complexes were obtained from the corresponding NHC–AgI. The lability of the NHC–Ln II bond was investigated and treatment with CO2 led to insertion reactions without oxidation of the metal centre. The Eu II complex [EuI2 (IMes)(THF)3 ] (IMes = 1, 3-dimesitylimidazol-2-ylidene) exhibits photoluminescence with a quantum yield reaching 53%.